Somophilic Isocyanide Insertion: Synthesis of 6-Arylated and 6-Trifluoromethylated Phenanthridines - Wang, Ruzhi; Jiang, Heng; Cheng, Yuanzheng; Kadi, Adnan A.; Fun, Hoong-Kun; Zhang, Yan; Yu, Shouyun (Synthesis, 2014)
A visible-light-promoted biaryl isocyanide insertion reaction has been developed to synthesize phenanthridine derivatives. The insertion proceeds via a radical process, and diaryliodonium salts and Umemoto’s reagent were used as radical sources. A variety of 6-arylated, as well as 6-trifluoromethylated, phenanthridine derivatives were obtained smoothly in good to excellent yields under mild conditions.
Keywords: insertions; arylation; heterocycles; photoredox catalysis; trifluoromethylation; isocyanides